A case study of the collaborative design of business curriculum on the Slovenian-Italian border for intercultural management adult students - Buko, Svitlana; Selvelli , Giustina (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2025)
This case study examines the impact of cross-border business curriculum design in the Slovenian-Italian border region, focusing on a MA-level program in Intercultural Management delivered in the twin cities of Nova Gorica (Slovenia) and Gorizia (Italy). The program was co-designed to foster cross-border exposure and develop students’ competencies for navigating complex regional business environments. The instructional design was built on four key pillars (4-pillar ID model): collaborative curriculum design, contextualized learning, immersive cross-border exposure, and personalized learning, and was piloted with adult learners. The study was conducted in three phases (2022–2024). Phase one analyzed reflective narratives from 86 Slovenian MA business students; phase two used a short quantitative self-assessment of cross-border competencies; and phase three involved a pilot survey with 25 participants, using a pre- and post-test design. Findings indicate that this 4-pillar ID model of cross-border curriculum significantly enhanced students’ development across three competency domains: (A) Cross-Border Attitudes – increased openness and curiosity in intercultural contexts; (B) Cross-Border Knowledge – improved understanding of geopolitical dynamics, historical legacies, and legal-economic frameworks; (C) Cross-Border Skills – strengthened capabilities in conflict management, comparative thinking, and frame-shifting for intercultural business contexts. The pilot survey showed a measurable increase in students’ knowledge and attitudes following cross-border engagement. These findings suggest that cross-border curricula, when carefully designed, can foster essential competencies for business professionals operating in multicultural and transnational settings. The model has broad relevance and can be adapted by institutions in other border regions seeking to enhance regional integration through education.